2013
DOI: 10.1007/s10815-013-0098-7
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive implications of psychological distress for couples undergoing IVF

Abstract: Our data validate the concept of a "stressed couple". Adverse implications of a couple's psychological distress for gamete biology (longer duration of COH and lower FR with increasing distress) are suggested. Partner's depressive scores negatively correlated with IVF success. These findings suggest the importance of including partner's evaluation in studies that focus on effects of psychological stress on IVF outcome; future studies should examine whether interventions aimed at reducing psychological stress fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 52 publications
(56 reference statements)
0
26
0
Order By: Relevance
“…A systematic review has revealed that couples who underwent IVF treatment suffered from the stressful experience as dyads [45]. Also, the depression score of men has been identified as an independent predictor of a reduced likelihood of clinical pregnancy [46]. However, 13 out of the 20 (65 %) RCT studies in this review neglected the men of infertile couples.…”
Section: Discussionmentioning
confidence: 88%
“…A systematic review has revealed that couples who underwent IVF treatment suffered from the stressful experience as dyads [45]. Also, the depression score of men has been identified as an independent predictor of a reduced likelihood of clinical pregnancy [46]. However, 13 out of the 20 (65 %) RCT studies in this review neglected the men of infertile couples.…”
Section: Discussionmentioning
confidence: 88%
“…Women who passed these stages but experienced a failure in treatment stated that they felt insufficient, empty, an absence, guilty, sad, like a failure, and deep sorrow. [29][30][31] In this study, these factors effectively promoted a high level of…”
mentioning
confidence: 75%
“…The opposite statements are 1,2,5,8,21,26,27,30,33,36, and 39 on the Trait Anxiety Inventory (TAI). After determine the total scores of the direct and opposite statements separately, the total weight score of the opposite statements are subtracted from the total weight score of the direct statements.…”
Section: State-trait Anxiety Inventorymentioning
confidence: 99%
“…Various studies exist highlighting the influence of both partners’ psychological variables with regard to infertility-related stress, anxiety, depression and coping, as experienced by infertile couples undergoing assisted reproductive technology treatment ( Benyamini et al, 2009 , Donarelli et al, 2012 , Martins et al, 2014 , Peterson et al, 2008 , Peterson et al, 2014 ); however, to our knowledge, only a few studies ( Boivin and Schmidt, 2005 , Cooper et al, 2007 , Quant et al, 2013 ) have investigated the impact of both partners’ psychological condition and infertility-related stress on assisted reproductive technology-specific outcomes. For example, in the study by Boivin and Schmidt (2005) higher overall infertility stress, as measured by the Fertility Problem Stress Inventory, in men and women, plus a prolonged period of several years of infertility, was associated with a poorer treatment outcome.…”
Section: Introductionmentioning
confidence: 99%